Aerobic condition enhances bacteriostatic effects of silver nanoparticles in aquatic environment: an antimicrobial study on Pseudomonas aeruginosa - Zhaoyu Chen (Nature Portfolio, 2017)
Abstract The intensive applications of silver nanoparticles (AgNPs) inevitably cause continuous release of such materials into environments, as a consequence posing potential risks to microbial communities in engineered or natural ecosystems. However, the magnitude of antibacterial capacity of nanoparticles is still inconclusive, owing to influential factors such as the size of nanoparticle, microbial species, or environmental conditions. To reveal whether the presence of air would alter AgNPs ecotoxicity, Pseudomonas aeruginosa PAO1, a facultative denitrifying bacterium and an opportunity pathogen, was used to study antibacterial assays under both anaerobic and aerobic conditions. The results indicate that the respiration status of P. aeruginosa affect the ecotoxicity of AgNPs. P. aeruginosa cultured under aerobic condition were more susceptible to AgNPs than that under anaerobic condition. Aerobic condition greatly enhanced bacteriostatic effects of AgNPs but not their bactericidal effects, as the ratio of viable but nonculturable (VBNC) bacteria remained above 90% when 5 mg L−1 AgNPs applied. Our findings offer further understanding for the degree of toxicity of nanoparticles on microbial ecosystems and underscore the importance of exposure condition (e.g. oxygen) in the mode of action of AgNPs.